Institutional ownership, free cash flow, collateral assets, and return on assets on dividend policy with debt policy as intervening variable - Irwansyah Irwansyah; Putri Maharani (INOVASI, 2022)
The aims of this research to get empirical evidence about the impact of institutional ownership such as free cash flow, collateral assets, and return on assets on dividend policy through debt policy as an intervening variable. The population in this research is consumer goods industry who had register in Indonesia Stock Exchange 2013-2020 period. The sample of this research shows that institusional ownership and collateral assets have a positive effect dan insignificant on debt policy. Next is institusional ownership, collateral assets and roa have a positive effect and insignificant on dividend policy. While free cash flow have a positive effect and significant on debt and dividend policy. After that roa have negative effect and significant on dividend policy, and also have a negative effect for debt policy and significant on dividend policy. The ownership of institutional, free cash flow, collateral assets and roa has no effect on dividend policy through debt policy.